Boosting the nation against covid-19: are the vaccination targets feasible?. (15th December 2021) - Osama, Tasnime; Hodes, Simon; Razai, Mohammad S; Majeed, Azeem
Abstract : What are the practicalities of delivering more than one million covid-19 vaccine doses a day?